PERBANDINGAN KECEPATAN BERPIKIR DAN PRIMA VISTAANAK MELALUI KAJIAN INSTRUMEN FLUTE - Ardi Magara, Achmad Nurulloh, dan Fransiska Heni Pangesti (Pelita - Jurnal Penelitian Mahasiswa UNY, 2011)
The aim of the research was to find out the difficulties of conducting individual assessment of primavista with a flute instrument and to the techniques of doing prima vista which was good and appropriate.The method used was experimental method. It was a method used to reveal a causal link of two ormore variables by controlling the influence of other variables. The method was implemented by using anindependent variable intentionally to object to the result in the dependent variable.It was concluded that the revealed an indispensable prima vista by a teacher in the teaching andalso by a professional artist. So, a teacher was able to introduce a piece of music to their students in amore real condition.Key words: prima vista, quick thinking, sight‐singing